Chapter Una slavista italiana dimenticata. Umberta Griffini, traduttrice, mediatrice e scrittrice - Banjanin, Ljiljana (Biblioteca di Studi Slavistici, 2018)
Umberta Griffini (1880-1956) may be considered one of the most important figures in Italian Serbo-Croatian Studies before these were formally established. Although she spent a decade, at the beginning of the 20th century, vigorously disseminating Serbian literature, in numerous writings, reviews and a large number of translations of Serbian authors, her work has received insufficient scholary attention. The aim of this article is to shed some light on an interesting woman who was atypical in the Italian cultural panorama of the first decade of the 20th century.